Coastal cities governance in the context of integrated coastal zonal management: a sustainable development goal perspective under international environmental law for ‘coastal sustainability’ - Zhang, Shijun; Wu, Qian; Butt, M. Jahanzeb; Lv, Yan-Ming; Wang, Yan-E- (Frontiers in Marine Science, 2024)
Literature on integrated coastal zonal management (ICZM) for coastal sustainability from a legal perspective provided significant measures. Recently, sustainable development goals (SDGs) have become a focus in ICZM literature, which establishes coastal goals and connects these goals with other goals. Although integrating coastal goals into ICZM under international law challenges the existing models presented in the literature, the comprehensive literature review (CLR) methodology is appropriate for observing the current literature and provides a way-forward for coastal goals. Therefore, through this research, a CLR on ICZM literature is conducted to observe how far SDGs are integrated for coastal sustainability. The CLR identified that coastal city governance is a pertinent part of ICZM, and the coastal goals are devised in the form of environmental goals of SDG – 14 (life below water). This CLR examines the anthropogenic connections of waste, sanitation, and emissions management and urban planning with coastal ecosystems under the ICZM system. For such purposes, governance tools of science-policy integration under international law and policy for sustainable development are utilized to form an obligatory framework. The CLR further provided coordination, adaptivity, monitoring, and capacity-building tools, which were utilized thoroughly throughout the literature and can be incorporated with the SDGs in a multilevel governance framework of ICZM. Throughout the study, international law formulating SDGs is pivotal to be transplanted successfully into the ICZM governance processes.